Parent’s Involvement in the Education of their Children who have Intellectual Disability: Perception and Knowledge - Alhossyan , Fawaz (Journal of Ecohumanism, 2025)
The purpose of the study was to investigate the knowledge and attitudes of parents with children who have intellectual disabilities (ID) regarding special education and inclusive education programming. The study employed a qualitative approach that involved semi-structured interviews with four parents of children with intellectual disability who are attending private and public special education schools in Saudi Arabia. The findings indicate parents have diverse and generally positive opinions regarding different aspects of the education and educational services their children who have intellectual disability. Through the coding and analysis of their responses to the 20 interview questions, four themes emerged, which were: Information and Knowledge About Special Education and Inclusion, Communication, the Individualized Education Program (IEP), and Assessment and Instruction. The parents also indicated a desire for stronger communication practices between school and home to better support their students with disabilities. Based on the results, it is recommended that further research on the communication processes between school personnel and parents/caretakers be conducted to identify best practices for achieving good communication for the benefit of students with intellectual disabilities.